2017
DOI: 10.1007/s12010-017-2486-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Brown Midrib Sorghum Mutants as a Potential Biomass Feedstock for 2,3-Butanediol Biosynthesis

Abstract: Three sorghum backgrounds [Atlas, Early Hegari (EH), and Kansas Collier (KC)] and two bmr mutants (bmr6 and bmr12) of each line were evaluated and compared for grain and biomass yield, biomass composition, and 2,3-butanediol production from biomass. The data showed that the bmr6 mutation in EH background led to a significant decrease in stover yield and increase in grain yield, whereas the stover yield was increased by 64% without affecting grain yield in KC background. The bmr mutants had 10 to 25% and 2 to 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…Typically, lignin content of groundnut shell is around 26.4% as reported by Patricia et al [29]. However, the plant lignin content is significantly affected by its genotype as well as the environment in which the plant is cultivated [30]. Boonmee reported 35.2% lignin content in peanut shell [31], which is in close agreement with our reported values.…”
Section: Biomass Compositionsupporting
confidence: 91%
“…Typically, lignin content of groundnut shell is around 26.4% as reported by Patricia et al [29]. However, the plant lignin content is significantly affected by its genotype as well as the environment in which the plant is cultivated [30]. Boonmee reported 35.2% lignin content in peanut shell [31], which is in close agreement with our reported values.…”
Section: Biomass Compositionsupporting
confidence: 91%
“…Evidence in this study suggest that the sweet mutation not only improves the SSC quality trait, but the stover yield of bmr , high sugar recombinant sorghum lines is increased, boosting theoretical ethanol production. This is especially noteworthy because most recent studies (Marsalis et al, 2010; Gill et al, 2014; Guragain et al, 2017; Kumar et al, 2018) confirm those reported previously (Oliver et al, 2004; Pedersen et al, 2005) regarding the inferior and/or variable agronomic performance of most sorghum lines with the bmr trait. This shortcoming has slowed deployment of this trait in both the forage and bioenergy sectors of agriculture.…”
Section: Discussionsupporting
confidence: 84%
“…It is worth noting that, unlike certain mutants affected in other steps of the lignin biosynthetic pathway, several CAD mutants do not show any visible phenotype or biomass yield penalty. This is the case for greenhouse-grown switchgrass (39,49) and field-grown corn (50, 51), poplar (52), and sorghum (53), although genotype-dependent variations have been observed for the latter (54,55). It is also important that DES-based catalyst-free pretreatment of transgenic biomass could lower chemical use and energy inputs typically required for the production of intermediate sugars, which can be further processed into value-added products.…”
Section: Discussionmentioning
confidence: 99%